2016
DOI: 10.2134/cs2016.49.0315
|View full text |Cite
|
Sign up to set email alerts
|

Cover crops can affect subsequent wheat yield in the Central Great Plains

Abstract: This research documented water use, grain yield, and water use efficiency of wheat following a 10‐species cover crop mixture and single‐species plantings (planted no‐till into proso millet residue) compared with winter wheat following a no‐till fallow period. The study was conducted under varying water availability conditions in western Nebraska and northeastern Colorado. Earn 0.5 CEUs in Soil & Water Management by reading this article and taking the quiz at http://www.certifiedcropadviser.org/certifications/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
3
5
0
Order By: Relevance
“…The 126-d samples were taken after the seeding of cover crops. Similar results were observed on the previous study, which showed that cover crops reduced SWS compared with no cover crop treatment (Gabriel et al, 2012;Nielsen et al, 2016). Another reason could be due to enough precipitation occur in the month of September.…”
Section: Infiltration Ratesupporting
confidence: 90%
See 2 more Smart Citations
“…The 126-d samples were taken after the seeding of cover crops. Similar results were observed on the previous study, which showed that cover crops reduced SWS compared with no cover crop treatment (Gabriel et al, 2012;Nielsen et al, 2016). Another reason could be due to enough precipitation occur in the month of September.…”
Section: Infiltration Ratesupporting
confidence: 90%
“…Similar results were observed in another study conducted in Iowa where long-term (>14 yr) use of winter rye CC increased soil water storage (Basche et al, 2016b). Several previous studies showed that cover crops can reduce water availability for next crops in semiarid and water limited areas (Nielsen et al, 2015;Nielsen et al, 2016). However, another study conducted in Iowa showed that winter cover crops increased SWS during the drought of 2012 (Daigh et al, 2014).…”
Section: Infiltration Ratesupporting
confidence: 80%
See 1 more Smart Citation
“…Although not significant in Ds/Do, residues of cereal rye, as well as corn from the previous year, could help in the reduction of evapotranspiration from surface soil, indicating a potential increase in bio-pores [51,58]. Similar results were reported by Nielson et al [59] and Basche et al [60] that cover crops can reduce water availability for the next crops in water-limiting conditions. Figure 3b shows that the inclusion of a cereal rye and no tillage increased Ds/Do at 10-20 cm depth compared to other treatment combinations.…”
Section: Effects Of Tillage System Cover Crop and Crop Rotation On Relative Gas Diffusion Coefficientsupporting
confidence: 73%
“…In this review, we focused specifically on water retained at field capacity and permanent wilting point and not on actual field water content. Available studies reporting actual field water content generally indicate that CCs can reduce water for the next crop in semiarid regions (Holman et al., 2018; Meyer, Bergez, Constantin, & Belleville, 2020; Nielsen, Lyon, Hergert, Higgins, & Homan, 2015, 2016; Unger & Vigil, 1998), whereas in regions with high precipitation CCs do not generally reduce water required for the subsequent crop. Indeed, in regions with high precipitation, the use of water by CCs can be beneficial to reduce excess soil water (Blanco‐Canqui et al., 2011; Kahimba, Ranjan, Froese, Entz, & Nason, 2008).…”
Section: Do Cover Crops Enhance the Ability Of The Soil To Retain Water?mentioning
confidence: 99%